2005
DOI: 10.1111/j.1469-8137.2005.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization and functional analysis of novel 6‐kestose exohydrolases (6‐KEHs) from wheat (Triticum aestivum)

Abstract: Summary• Cereals accumulate graminan-type fructans which are subject to stress-related degradation by fructan 1-exohydrolases (1-FEHs) and fructan 6-exohydrolases (6-FEHs). To find new FEH genes related to freezing tolerance, a cold-hardened wheat crown cDNA library was screened.• Here we report the cloning, purification and characterization of two novel 6-kestosidase (6-KEH) isoenzymes from wheat crowns ( Triticum aestivum ). Functional characterization in Pichia pastoris confirmed the extreme substrate selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 73 publications
(129 reference statements)
1
60
0
2
Order By: Relevance
“…Fructan is hydrolyzed to Fru and Suc by fructan 1-exohydrolase (1-FEH) and/or fructan 6-exohydrolase (6-FEH; Van den Ende et al, 2005;Van Riet et al, 2006). The transcript levels of TaFEH genes did not appear to be associated with genotypic variation in the stem WSCs at anthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Fructan is hydrolyzed to Fru and Suc by fructan 1-exohydrolase (1-FEH) and/or fructan 6-exohydrolase (6-FEH; Van den Ende et al, 2005;Van Riet et al, 2006). The transcript levels of TaFEH genes did not appear to be associated with genotypic variation in the stem WSCs at anthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Kawakami and Yoshida 8,9 cloned 4 cDNAs that cover all kinds of fructan synthetic enzymes in wheat. Several clones of wheat fructan exohydrolases, 1-FEH 22,25 , 6-FEH (6-KEH) 23,24 , and 6&1-FEH 10 , have been isolated and functionally analyzed. Plant fructosyltransferases and fructan exohydrolases show high homology to vacuolar and cell-wall invertases, respectively (Fig.…”
Section: Molecular Characteristics Of Genes Coding Enzymes For Fructamentioning
confidence: 99%
“…Enzymes that preferentially degrade fructan trisaccharides were recently discovered in fructan plants. Specific 6-kestosidase (6-KEH) enzymes have been purified and cloned from wheat (Triticum aestivum; Van den Ende et al, 2005) and 1-KEH activities were reported in onion (Allium cepa; Benkeblia et al, 2005). Strikingly, the D239A mutant showed superior affinity (K m 600 mM) for 1-kestose compared to the naturally occurring FEHs from chicory (1-FEH IIa: 58 mM; De Roover et al, 1999) and wheat (1-FEH w1 and w2: 7 mM; Van den Ende et al, 2003a).…”
Section: Conserved Trp Residues Are Important For Stable Substrate Bimentioning
confidence: 99%